FORMATION OF INDEPENDENT THINKING OF STUDENTS USING INTERACTIVE METHODS IN HIGHER EDUCATIONAL INSTITUTIONS - Ulugmurodov Farkhod Faxriddinovich (Scholars Digest Publishing, 2023)
This article examines the formation of independent thinking of students using interactive methods in higher educational institutions. The article analyzes the importance of interactive teaching methods and their role in self-organization and assimilation by students. The article also provides information on how interactive methods contribute to the improvement of the learning process, the formation of critical thinking of students, problem solving, the development of the experience of interaction and cooperation between students.
Keywords: Interactive teaching methods, self-organization of students, assimilation, thinking, counseling, words, creative work, experimental work, group work, critical thinking, problems, cooperation, joint experience, training, assistance.